(untitled) (Physical Education, Health and Social Sciences, 2025)
Physical activity plays a vital role in children’s social development. This study demonstrates by examining its impact on teamwork, communication, and peer relationships. Using a quantitative research design, data were collected from 100 teachers across four schools to assess the influence of a structured physical activity programs. The participants’ responses were recorded using structured questionnaire. The data were analyzed using descriptive and inferential statistics, including ANOVA, Correlation, and t-test to assess the variation of responses. The results show a statistically significant relationship between physical activity and social skills (r=0.65, p=0.001), and a moderate association with behavioral outcomes (r =0.52, p =0.004). ANOVA results show significant differences between age groups (F =3.67, p =0.02) and activity levels (F =4.52, P =0.01), while no significant gender differences was found.The study advocates for integrating structured physical activity programs into school curricula to promote holistic development. This will be very helpful for schools, parents, teachers, and policymakers in developing physical activity programs for school-aged children.